2016
DOI: 10.3325/cmj.2016.57.287
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio help identify patients with lung cancer, but do not differentiate between lung cancer subtypes

Abstract: AimTo assess the diagnostic value of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in lung cancer (LC). We compared the ratios between healthy participants and all LC patients, as well patients with different pathohistological LC subtypes.MethodsWe retrieved the data on neutrophil, lymphocyte, and platelet levels in 449 patients with different pathohistological LC subtypes (non-small cell LC, small-cell LC, atypical or metastatic LC, neuroendocrine, and sarcomatoid carcinoma) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Indeed, high platelet count is associated with increased mortality in a variety of cancers, including malignant mesothelioma (11), gynecologic malignancies (12), and breast cancer (13). In addition, platelet-to-lymphocyte ratio and mean platelet volume also add value in early diagnosis of lung cancer (14) and prognosis prediction (15,16). These findings, taken together, indicate that disordered platelet production may be connected to lung carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high platelet count is associated with increased mortality in a variety of cancers, including malignant mesothelioma (11), gynecologic malignancies (12), and breast cancer (13). In addition, platelet-to-lymphocyte ratio and mean platelet volume also add value in early diagnosis of lung cancer (14) and prognosis prediction (15,16). These findings, taken together, indicate that disordered platelet production may be connected to lung carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has supported that systemic inflammation is related to shorter survival among patients with many cancers through promotion of cancer cell proliferation and survival, angiogenesis, and tumor metastasis [ 4 , 5 ]. Inflammation-based prognostic scores including platelet-to-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), Glasgow Prognostic Score (GPS) and mGPS have been reported to have prognostic efficacy for patients with cancers [ 6 , 7 ]. mGPS is a useful prognostic score for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was determined between the groups according to NLR and PLR. Nikolić et al [25] showed significantly higher NLR and PLR values in lung cancer patients (n=388) in comparison with a control group (n=47), but no difference was observed between subgroups of the lung cancer patients [25]. In the current study, NLR was significantly correlated with the SUV max ratios of spleen/aorta, spleen/liver, mass/aorta, mass/liver, and with the SUV mean ratios of spleen/aorta, bone marrow/aorta, spleen/ liver, and bone marrow/liver.…”
Section: Discussionmentioning
confidence: 99%